PROFIL BIDANG PENGEMBANGAN BELAJAR PESERTA DIDIK DI SMP NEGERI 1 KECAMATAN BUKIT BARISAN KABUPATEN 50 KOTA - Monalisa, Sukma - (Bimbingan dan Konseling, 2014)
This researchis motivated by the presence of students who have alow learning outcomes are less active in class, participate less on learning activities, lack of paying attention, concentration and uncomfortable with the lessons inclass, talking with friends or day dreaming bench when learning take splace, less serious about the task, are less interested to learn, do not want and do not dare to speakup in class, do not want to changethe bad habits learned that despite having given assistance by the teacher BK. The purpose of this study describe 1) Profile motivation of learners 2) an interest profile of learners 3) impaired concentration profile of learners. This research is descriptive quantitative research. The population total enrollment in the District 1 Junior High School Bukit Barisan District 50 City there 172 students, and the sample amounted to 83 people. Sampling using proportionate stratified random sampling technique. The technique used to analyze the data is the mean hipotetic formula. The result of this study found that: 1) Profile motivation of learners in middle category, 2) an interest profile of learners in middle category, 3) Profile impaired of learners in the middle category. Based on the finding of this study recommended tostudents, get solution of learners problems related to learning motivation, learning interest and learning impaired concent